2007
DOI: 10.1258/096914107782912103
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling mammography screening for the early detection of breast cancer in Korean women

Abstract: Objective To propose an efficient screening schedule for breast cancer among Korean women using the stochastic model in which the age-specific incidence rate was considered. Setting Female breast cancer data in the Korea Central Cancer Registry 2002. Methods The stochastic model was based on the threshold method, in which the schedule is determined by a pre-specified threshold value. The threshold value was defined as the probability of being in a preclinical state of breast cancer at age 40 years. The sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Screening mammography and use of ultrasonography play an important role in detection of breast cancers in earlier stages (17). Since 1996, it was recommended that all Korean women over 40 yr old underwent a mammography every 1 or 2 yr (18). From 1996 to 2004, the incidence of stage 0 and I breast cancers increased remarkably by 128.6% and 81.6%, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…Screening mammography and use of ultrasonography play an important role in detection of breast cancers in earlier stages (17). Since 1996, it was recommended that all Korean women over 40 yr old underwent a mammography every 1 or 2 yr (18). From 1996 to 2004, the incidence of stage 0 and I breast cancers increased remarkably by 128.6% and 81.6%, respectively (16).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions are provided in our previous study. ( 15 ) Incidence rates were calculated for each age group and ranged from 0 to 4 years of age to more than 85 years of age. The cost estimates of the mammography and the confirmative examination were obtained from the National Health Insurance Corporation of Korea in 2007.…”
Section: Methodsmentioning
confidence: 99%
“…( 18 ) To estimate the total cost, we defined the unit cost of the mammography, the unit cost of the confirmative tests, and the specificity of the mammography as US$19.50, US$171.90, and 0.95, respectively. ( 15,20 ) To evaluate the robustness of the proposed screening strategies, one‐way sensitivity analyses were conducted by changing the MST in the preclinical state, the sensitivities and the specificities of the mammography, costs, and discount rates. The study parameters are shown in Table 2 with their references.…”
Section: Methodsmentioning
confidence: 99%
“…Screening programs have been established in Western countries and are being developed around the world, including some Asia–Pacific countries, although there is wide variability in the presence and recommendations of the programs in this region (Table 2). 22,39,40,45–48 In Singapore, population‐based screening was started after a trial program in which 166 600 women aged 50–64 years were randomized to screening by mammography or observation, demonstrated an increase in breast cancer detection from 1.3–4.6 per 1000 women 49 . Through the BreastScreen Singapore program, women aged 40–49 years receive annual mammography while women 50 years of age or older undergo biennial examination at a subsidized rate 38 .…”
Section: Screeningmentioning
confidence: 99%